Refression and other stories - Gelman, Andrew; Hill, Jennifer (New York Cambridge, 2021)
Most textbooks on regression focus on theory and the simplest of examples. Real statistical problems, however, are complex and subtle. This is not a book about the theory of regression. It is about using regression to solve real problems of comparison, estimation, prediction, and causal inference.